Biophysical variables in fertile islands of the Argentinian Arid Chaco - Karlin, Marcos Sebastián; Coirini, Rubén O.; Contreras, Ana Marina; Ringuelet, Ariel; Bernasconi Salazar, Javier R.; Cora, Amanda; Buffa, Eduardo V. (2024)
Poster